Assistance The Drafting Of Permanent Employee Letter And Fixed-Term Work Contract In Pt Sukses Media Kreatif - Irene Irene (Universitas Internasional Batam, 2021)
Regulations of specified period and unspecified period work agreement was formed as a guarantee of the working relationship existence in a company between the employer and the employee. In the world of legal practice, this work agreement is usually realized in the form of a permanent employee letter of appointment for the unspecified period work agreement and a fixed-time work contract fix the specified period work agreement. This work agreement is crucial to exist because if an industrial dispute occurs, the two parties can refer back to the agreed and signed agreement. However, even though the regulation exists, it is still common to find companies that do not implement work agreements following the Law Number 13 of 2003 concerning Manpower. PT Sukses Media Kreatif is a start-up company that utilises the social media as a platform for social media marketing. This company offers social media marketing services which include marketing strategies and an interactive media in the form of videos and photos as the promotional content. This company consists of management and employees, whom are young fresh graduates. Thus, the problem of ethical work discipline becomes a problem since no regulation has been established yet. This research was conducted to resolve the legal issues that exists in the company, which is the absence of work agreements in the existing work relationship. The research method uses applied research that offers applied solutions to legal problems in PT Sukses Media Kreatif after an observation, problem finding, literature, and regulation study related to agreements in general and work agreements.